2021
DOI: 10.3389/fmars.2021.658361
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Dependent Effects of Di-(2-Ethylhexyl) Phthalate (DEHP) in Mussel Mytilus galloprovincialis

Abstract: Phthalic acid esters (PAEs) are environmental organic pollutants that are ubiquitous in the ocean, and di-(2-ethylhexyl) phthalate (DEHP) is the most widely used PAE. The environmental concentration of DEHP was reported to be up to 42.52 μg/L in seawater in the estuaries located in Jiaozhou Bay along the Yellow Sea. DEHP has been investigated with respect to its toxicity in marine organisms. However, evidence on the dose-dependent effects of DEHP remains contradictory and limited. We used marine mussel Mytilus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…DEHP, a plasticizer used in various plastic products, is one of the most common PAEs detected in the environment and especially in the marine environment, where it derives mainly from rivers' input and chemical and physical degradation of plastic litter (Selvaraj et al, 2015;Paluselli et al, 2018;Zhang et al, 2021). DEHP causes immunotoxicity, metabolic toxicity, neurotoxicity, and endocrine toxicity in both terrestrial mammals (Chang et al, 2017;Radke et al, 2020;Weaver et al, 2020) and aquatic organisms (Molino et al, 2019;Yu et al, 2019;Xu et al, 2021;Zhang et al, 2021). In the current study, results of in vitro exposure to DEHP on TT and CHO cell lines highlighted cytotoxic and genotoxic effects, confirming that this phthalate constitutes an important threat to both marine and terrestrial mammals.…”
Section: Discussionmentioning
confidence: 99%
“…DEHP, a plasticizer used in various plastic products, is one of the most common PAEs detected in the environment and especially in the marine environment, where it derives mainly from rivers' input and chemical and physical degradation of plastic litter (Selvaraj et al, 2015;Paluselli et al, 2018;Zhang et al, 2021). DEHP causes immunotoxicity, metabolic toxicity, neurotoxicity, and endocrine toxicity in both terrestrial mammals (Chang et al, 2017;Radke et al, 2020;Weaver et al, 2020) and aquatic organisms (Molino et al, 2019;Yu et al, 2019;Xu et al, 2021;Zhang et al, 2021). In the current study, results of in vitro exposure to DEHP on TT and CHO cell lines highlighted cytotoxic and genotoxic effects, confirming that this phthalate constitutes an important threat to both marine and terrestrial mammals.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of DEHP on Mytilus spp. range from alterations in antioxidant and peroxisomal enzyme activities at high levels of 100–500 µg/L (Cancio et al 1998 ; Orbea et al 2002 ) to hormetic effects on the expression of oestrogen receptor-like (Mincarelli et al 2021 ) and stress-related genes (Xu et al 2021 ) when environmentally relevant concentrations are dosed. In fact, the nonmonotonic dose–response action of some endocrine active chemicals such as DEHP can provoke a stronger effect at low concentrations and inhibition at higher levels (Conolly and Lutz 2004 ; Do et al 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…A further survey of the literature for the purpose of this study revealed ample evidence suggestive of hormesis for numerous aquatic organisms and various pollutants and emerging contaminants in dozens of publications, of which only a few selected examples are cited here (older examples can also be traced in the therein references). These examples include a plethora of species, such as of algae (microphytes) [38][39][40][41][42][43][44][45][46][47][48][49] , aquatic flowering plants [50] , organism-attached biofilms [51] , crustaceans [52][53][54][55][56][57] , cyanobacteria [49,[58][59][60][61] , fishes [62][63][64][65][66][67][68][69] , macrophytes [70][71][72][73][74][75] , marine polychaete [76] , mollusks (e.g., clams and mussels) [77,78] , periphyton [79] , phytoplankton [80] , sea anemones [81,82] , and snails [83] . Responses suggestive of hormesis were found for molecular (molecules...…”
mentioning
confidence: 99%
“…Responses suggestive of hormesis were found for molecular (molecules involved in oxidative stress), cellular (e.g., growth and density), and whole-organism (e.g., growth and body mass) endpoints, as well as endpoints suggesting potential sub-NOAEL effects on organismic interactions, such as via altered feeding activity [83] . Such responses were induced by chemicals such as antibiotics/antifungals [38,39,42,45,50,51,67,70,71,75] , steroid hormones [41,83] , and other human drugs [63,69] , bisphenol A and its substitutes [66] , chemical leached from disposed light sticks [55] , electroplating processemitted particulate matter [40] , effluents from textile-dyeing wastewater treatment plants [46] , fullerene crystals (nC 60 ) [57] , metals and ionic liquids [62,77,81,82] , micro/nanoplastics and their leachates [43,44,47,53,60,64,80,84] , engineered nanomaterials [58,59,61,65] , pesticides [48,49,52,56,[72][73][74]79,84] , phthalic acid esters ...…”
mentioning
confidence: 99%